Analisis Perhitungan Upah Kerja Lembur (Overtime) dan Insentif pada Sistem Penggajian PT NOK Precision Component Batam - Fika Nia Ariska (Politeknik Negeri Batam, 2014)
The purpose of this research is to know about the overtime calculation in employee on level staff and non-staff also about the given of incentive or allowance to motivate all the employee so they can work better than before. The methods used for this research is observation and analysis. The observation method used when writer directly look into the payroll system to see and calculate overtime recapitulation, while the analysis method used when writer directly calculate the overtime wage based on data taken from recapitulation. The result of this research is the calculation of the wage multiplication per hour calculated based on KEPMEN NO.102 year 2004, while overtime rate that was used to be the base of the calculation for nominal wages that get per hour is calculated through overtime rate that was on the calculation component plus position allowance that only given to employees that have Assistant Team Leader position and above. For incentive given that already set by NOK Precision Component Batam Corporation Management was given to all employees that work in the company except other allowance given only on certain level and certain section.